Enhancing indoor photovoltaic performance of inverted type organic solar cell by controlling photoactive layer solution concentration; [Meningkatkan prestasi fotovoltaik dalaman sel suria organik jenis terbalik dengan mengawal kepekatan larutan lapisan fotoaktif] - Wajidh, Mohamed Nafeer; Issa, Nour Attallah; Lau, Kam Sheng; Tan, Sin Tee; Chia, Chin Hua; Mustapha, Muslizainun; Jumali, Mohammad Hafizuddin; Yap, Chi Chin (Penerbit Universiti Kebangsaan Malaysia, 2024)
With the development of various low-power indoor electronic devices, indoor photovoltaics, particularly organic solar cells (OSCs) have attracted a lot of interest in recent years. Increasing the light absorption and suppressing the leakage current are pivotal to improve the indoor photovoltaic performance of OSCs. In this study, the carbon quantum dots (CQDs)-incorporated photoactive layer solution concentration was varied to improve the photovoltaic performance under 1-sun and indoor white LED illumination. The photoactive layer was composed of (6,6)-phenyl-C61-butyric acid methyl ester) (PCBM) as the acceptor and poly(3-hexylthiophene) (P3HT) as the donor. The ZnO electron transport layer was deposited on fluorine-doped tin oxide (FTO)-coated glass substrates using a spin coating technique. The photoactive layers with different solution concentrations were spin coated on top of the ZnO layer. For device completion, silver anode was thermally evaporated. It is interesting to find that the optimum solution concentration obtained under white LED illumination is larger than that under 1-sun illumination. The maximum power conversion efficiency (PCE).of 0.95% was obtained under 1-sun illumination for device with the solution concentration of 36 mg/mL, whereas, under white LED illumination, the highest PCE of 3.59% was obtained for the device with solution concentration of 48 mg/mL. The discrepancy is ascribed to the higher light absorption of thicker photoactive layer and less significant charge recombination loss under weak light intensity. This study highlights the importance of using different optimization strategies to improve the photovoltaic performance of OSCs for outdoor and indoor applications. © 2024 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.